Learning Effectiveness in Year-Round Hajj Manasik Guidance: A Case Study in Gowa Regency, South Sulawesi - Sri Ilham Lubis (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This study addresses the limited effectiveness of conventional, ten-session, lecture-centric Hajj Manasik for pilgrims of diverse ages and schooling by evaluating a year-round manasik program at KUA Somba Opu (Gowa). Methods used a descriptive design combining observation, interviews, and pre–post questionnaires in 2022 with 107 participants (of 163) and 15 instructors; measures covered understanding of pillars, obligations, procedures, and timing, plus perceived benefits and barriers through an andragogical lens. The Results of this study show comprehension rose markedly.